Development of Constructivist Learning Model in Research Methodology Lectures - Wahyuningsih, Wiwin Arbani; Indrayanto; Utami, Henny Septia (LETIGES, 2025)
This study aims to analyze the obstacles and identify effective strategies to develop a prototype learning model that enhances students’ understanding of research methodology in higher education. At IAIN Curup, a 2023 internal survey involving students from four study programs (PGMI, PAI, MPI, and English Language Teaching) revealed that 72% of students struggled with fundamental research concepts, while 65% lacked confidence in using data analysis software such as SPSS and NVivo. This research employed a qualitative approach, using in-depth interviews and field observations involving both students and lecturers who are actively involved in teaching research methodology. The research was conducted from September to November 2024 at IAIN Curup, located in Rejang Lebong Regency, Bengkulu Province. This institution was selected because it actively implements research methodology courses across various academic programs. The subjects of this research include ten lecturers who teach research methodology and twenty students who have completed the course. The collected data were analyzed using thematic analysis. The analysis included several stages: data transcription, coding, categorization, and interpretation. The study found several key barriers, including limited comprehension of basic methodological concepts, low motivation, and difficulties in applying data analysis tools. External challenges include inadequate supporting facilities, restricted access to scientific literature, and time constraints. Based on these findings, the study proposes a prototype learning strategy that combines practice-based learning, integrated software workshops, and strengthened mentoring systems. This prototype was found to significantly increase student engagement and comprehension during pilot implementation. This study is limited to a single institution and a relatively small sample size, which may affect the generalizability of the findings. Further research is needed to test the prototype across multiple institutions.